Rural and urban dynamics and poverty: Evidence from China and India - Fan, Shenggen; Chan-Kang, Connie; Mukherjee, Anit (International Food Policy Research Institute, 2005)
Like many developing countries, China and India followed development strategies biased in favor of the urban sector over the last several decades. These development schemes have led to overall efficiency losses due to misallocation of resources among rural and urban sectors. It also led to large income gaps between rural and urban areas. The urban bias was greater in China than in India. Indeed, official data show that both the income gap and the difference in poverty rates between rural and urban areas are much larger in China than in India. Both countries have corrected the rural-urban divide to some extent as part of reform processes. But the bias still exists. Other studies also support the idea presented here that correcting this imbalance will not only contribute to higher rural growth, but also secure future urban growth (Fan and Chan-Kang 2005). More important, correcting the urban bias will lead to larger reductions in poverty as well as more balanced growth across sectors and regions. Correcting a government’s bias towards investment in urban areas is one of the most important policies to pursue.